Passive Sociopathy - Ilievski, Naum; Angelina Ilievska (European Journal of Multidisciplinary Studies, 2020)
In the domain of complex relational phenomena and social behaviors, passive sociopathy (N. Ilievski) is described as a form of inadequate behavior with a negative impact not only in the immediate, but also in the wider social context as a global psycho-social phenomenon. This dysfunctional pattern is an indicator of psycho-social distortion with unproductive to extremely passive and risky behavior. Analysis and description of this phenomenon through the three psychological components: emotional, cognitive, and behavioral, in correlation with exogenous factors and influences, from the aspect of Christian psychotherapy and the model of Transactional analysis. The practice of Christian psychotherapy sets prayer as a central point of the FCP method in cultivating empathy as a dimension of emotional intelligence through which an emotionally healthy base is built in the person with adequate prosocial behaviors. Contemporary man, faced with the challenges of modern trends – in which the mass media of hyper information plays an important role – is flooded with negative information that changes the threshold of his perception and sensitivity to the level of discount, emotional dullness, to extreme insensitivity as the main characteristic of passive sociopathy.